Alveolar echinococcosis of the liver: percutaneous stent therapy in Budd-Chiari syndrome. Issue 5 (November 1996) - Vogel, J; Görich, J; Kramme, E; Merkle, E; Sokiranski, R; Kern, P; Brambs, H J
Abstract : BACKGROUND AND AIMS: Infiltration of the hepatic veins in the alveolar echinococcosis can lead to the development of the Budd-Chiari syndrome. The medical and surgical treatment of this condition is generally unsatisfactory. The results of successful interventional treatment with percutaneous stent implantation in the hepatic veins are reported. METHODS: Using a transjugular approach, metal mesh stents (Boston Scientific, Medi-Tech Accuflex 8/60 mm) were placed in the median and left hepatic veins of a 53 year old woman. After the intervention, oral chemotherapy with albendazole (2 x 400 mg/day) was continued, but no anticoagulants were given. RESULTS: Stent placement was performed without complications. The clinical picture improved rapidly: normalisation of portal blood flow was confirmed by Doppler ultrasound and there was improvement of liver function, reduction of oesophageal varices, and disappearance of ascites. A follow-up examination at 15 months showed no evidence of stent occlusion. CONCLUSIONS: Treatment of portal hypertension in alveolar echinococcosis of the liver is problematic. In selected patients with portal hypertension secondary to hepatic vein stenoses but no cirrhosis, percutaneous stent placement in the hepatic veins represents a promising treatment alternative.